The Influence of Financial Report Quality on Performance Accountability in the Regional Financial Management Agency of Mamasa Regency - Rusdiah Hasanuddin; Nadya Nurhidayah Nurdin; Nurasia Natsir (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study employs a quantitative methodology to evaluate the impact of financial report quality on performance accountability within the Regional Financial Management Agency of Mamasa Regency. Data was collected through a structured questionnaire distributed to all agency employees, ensuring a comprehensive understanding of their perspectives. The analysis utilized hypothesis testing and basic linear regression to derive meaningful conclusions from the data collected. The sample for this investigation comprised all 52 employees from the Regional Financial Management Agency, allowing for an inclusive representation of the population. The results of the hypothesis test yielded a significance value (Sig.) of 0.001, which is less than the threshold of 0.05. This statistical finding leads to the conclusion that the quality of financial reports (variable X) significantly influences performance accountability (variable Y) in the agency. These findings underscore the importance of maintaining high standards in financial reporting, as it directly correlates with enhanced accountability in performance. The study highlights the need for continuous improvement in financial report quality to foster greater transparency and responsibility within public financial management practices.